2022
DOI: 10.1111/myc.13431
|View full text |Cite
|
Sign up to set email alerts
|

Incidence and risk factors for COVID‐19 associated candidemia (CAC) in ICU patients

Abstract: Candidemia is one of the most common nosocomial bloodstream infections in critically ill patients, accounting for 7%-15% of the episodes, and is associated with increased mortality, prolonged hospital stays, and increased cost. 1,2 Non-neutropenic intensive care unit (ICU) patients undergoing multiple invasive procedures, and immunocompromised patients are at high risk for the development of candidemia. 3,4 The COVID-19 pandemic caused an increase in the number of patients who need to be followed up in ICU, cr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
23
1
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 19 publications
(27 citation statements)
references
References 33 publications
2
23
1
1
Order By: Relevance
“… 11 However, in all previous studies, multifocal candida colonisation rates in patients with candidemia were reported to be around 40–55%. 9 , 10 , 11 , 17 Therefore, there is a need to increase the predictive value on candidemia by evaluating risk factors together. Detection of multifocal colonisation is a useful predictor for candidemia, especially in patients with CVC.…”
Section: Discussionmentioning
confidence: 91%
See 3 more Smart Citations
“… 11 However, in all previous studies, multifocal candida colonisation rates in patients with candidemia were reported to be around 40–55%. 9 , 10 , 11 , 17 Therefore, there is a need to increase the predictive value on candidemia by evaluating risk factors together. Detection of multifocal colonisation is a useful predictor for candidemia, especially in patients with CVC.…”
Section: Discussionmentioning
confidence: 91%
“…This was a result we expected based on our previous study. 11 In Leon's Candida score study, the rate of corticosteroid use was similar in patients with unifocal/multifocal Candida spp. colonisation and those with proven candida infection (24.2% vs 22.7%), and corticosteroid use was not an independent risk factor for proven candida infection.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…Most of these patients have risk factors making them prone to fungal infections, such as hospitalization in the intensive care unit (ICU), high pres cription rates of broad-spectrum antibiotics, corticosteroid therapy, use of various catheters, underlying diseases, and immunodeficiencies. Among the opportunistic fungal infections, (e.g., Aspergillosis, Mucormycosis, and Candidiasis) the most common fungal co-infections during previous influenza pandemic outbreaks are now the most common fungal co-infections in COVID-19 patients (Meijer et al, 2020;Salehi et al, 2020;Fortarezza et al, 2021;Kayaaslan et al, 2021;Kayaaslan et al, 2022;Vaseghi et al, 2022).…”
Section: Introductionmentioning
confidence: 99%